IN VITRO SCREENING OF GROUNDNUT (ARACHIS HYPOGAEA L.) VARIETIES FOR DROUGHT TOLERANCE USING POLYETHYLENE GLYCOL (PEG 6000) (FUDMA JOURNAL OF SCIENCES, 2023)
Drought has been a major environmental factor contributing to reduced crop productivity. Identifying groundnut varieties that are drought tolerant will be of immense importance to the improvement of the crop. The study aimed at screening groundnut varieties for drought tolerance under in vitro condition using polyethylene glycol (PEG 6000). Treatments comprise of six varieties of groundnut (SAMNUT 14, SAMNUT 22, SAMNUT 23, SAMNUT 24, SAMNUT 25 andSAMNUT 26) and different concentration of PEG 6000 (0, 20, 40, 60g/L). The treatments were laid out in a Completely Randomized Design with three replications. Embryonic axes explants were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations of PEG for shoot formation. Data were collected on shoot lengths, number of leaves per plantlet, number of roots and root length. A significant (P
Keywords: Drought tolerance, groundnut, in vitro screening, PEG (6000)